Antibody Interactions with the Capsule of Cryptococcus neoformans - Feldmesser, Marta (American Society for Microbiology, 2000)
Monoclonal antibodies to the encapsulated fungus Cryptococcus neoformans produce different immunofluorescence (IF) patterns after binding to the polysaccharide capsule. To explore the relationship between the IF pattern and the location of antibody binding, two immunoglobulin M (IgM) monoclonal antibodies (MAbs) (12A1 and 13F1) that differ in protective efficacy and IF pattern and one protective IgG1 MAb (2H1) were studied by IF and electron microscopy (EM). Fixing C. neoformans cells in lung tissue for EM resulted in significantly better preservation of the capsule than fixing yeast cells in suspension. The localization of MAbs 12A1 and 13F1 by immunogold EM differed depending on whether the MAb was bound to cells in cut tissue sections embedded in plastic or to cells in solution. In cut tissue sections, MAbs 12A1 and 13F1 bound throughout the capsule, whereas in solution both MAbs bound near the capsule surface. To investigate whether antibody binding to the C. neoformans capsule affected the binding of other primary or secondary reagents, various combinations of MAbs 12A1, 13F1, and 2H1 were studied by direct and indirect IF. The IF pattern and location of binding for MAbs 12A1, 13F1, and 2H1 varied depending on the presence of other capsule-binding MAbs and the method of detection. The results show that (i) binding of MAbs to the C. neoformans polysaccharide capsule can modify the binding of subsequent primary or secondary antibodies; (ii) the IgM MAbs bind primarily to the outer capsule regions despite the occurrence of their epitopes throughout the capsule; and (iii) MAb 2H1 staining of newly formed buds is reduced, suggesting quantitative or qualitative differences in bud capsule.